Investigating the Effect of Winding Structures in Dynamic Wireless Power Transmission in Electric Vehicle Applications - M. Rafinejad; A. Ghayebloo (Iranica Journal of Energy and Environment)
In recent decades, problems such as air pollution and the reduction of fossil fuel resources led to the development of electric vehicles. Wireless power transmission is an efficient and reliable way to charge fixed and mobile electric vehicles. One of the main problems in the dynamic wireless power transmission method is the amount of constant power transmission and its fluctuations. The purpose of this paper is to compare six different types of winding structures for choosing the best type of winding for the transmitter side in the application of dynamic charging of electric vehicles. In this paper, the winding function method is used for more accurate modeling of coils in terms of spatial harmonics and calculation of their self and mutual inductances by changing the location of the vehicle. Also, for coil excitation, instead of using the common single-phase inverter, a three-phase type is used to reduce the power ripple. The comparison is made in the aspect of the transmission power amount and its ripple. Modeling and simulation results are presented to confirm the actual results.